Unlocking Work Engagement: How Leadership and Total Rewards Impact Employee Work Engagement Through the Mediating Role of Service Climate in Supply Chain and Logistic Company in Indonesia - Indra Fahrizal; Budi Santoso; Aris Budiono (Universitas Trunodjoyo Madura, 2023)
Although the supply chain and logistics sector in Indonesia is developing very well and contributes very significantly to the Indonesian economy, which is about 25% of Indonesia's total GDP (World Bank 2018), the industry is very competitive. To survive in this sector, companies must be able to compete through price, service quality, and product innovation. Work engagement can help employees remain focused, motivated, and productive in such a fast-paced and complex environment. The focus of this research is to confirm the effect of leadership, rewards, and service climate on work engagement and the mediating effect of service climate on work engagement. The sample of this study consists of 287 respondents who work in various divisions and branches of a logistics company in Jakarta, metropolitan Indonesia. The data is analyzed using the Smart PLS version 3.0 application. All of the research hypotheses were accepted, there for Leadership practices have a positive and significant effect on work engagement and service climate, Total Rewards have a positive and significant effect on service climate and work engagement, and Service Climate mediates the effect of Leadership practices and Total Reward on work engagement. It is expected the research findings can be used by the company to understand and improve their service delivery processes, enhance employee engagement and satisfaction, and ultimately increase customer satisfaction and loyalty, which are critical factors to survive in a competitive market.